Love and Guilt-Oriented Dimensions of Christian Belief - McConahay, John B. (Journal for the scientific study of religion, 1973)
Four dimensions of religious belief related to the Love-Guilt complex in Christian theology were proposed along with a fifth dimension of Conventionalism or culture-oriented belief. A universe of items thought to tap these dimensions was administered to 160 students from three seminaries in Southern California and the data were submitted to a Likert scaling technique. The final scales measured Guilt-oriented, Love-oriented (both Self-centered and Other-centered), and Culture-oriented (or Conventional) religiosity. Except for Conventionalism, the scales were essentially unrelated to the Allport-Ross Extrinsic and Intrinsic scales. All scales were unrelated to social class. The Guilt and Love-Self scales were positively related to each other and to Conventionalism. The Love-Other scale was negatively correlated with Guilt and uncorrelated with Love-Self and Conventionalism. The Love-Other scale was positively related to a Guttman-type scale of Attitudes Toward Church Involvement in Social Action, and the Allport-Ross Extrinsic scale was unrelated to Church Involvement. All other scales were negatively related to Church Involvement.